Study on Promoting Cabbage Growth with Diethy Amioethyl Hexanoate 5% AS - Weisong, Xu; Yilin, Huang; Zhenbiao, Zhou; Shuheng, Wen; Zhimin, Zhuang (Plant Diseases and Pests(植物病虫害研究：英文版), 2014)
Field efficacy trials showed that Diethy Amioethyl Hexanoate 5% AS could promote growth and increase yield of cabbage. The cabbage yield increase rate was up to 40.37% by using reagent dilution 2 000 -2 500 times twice, so Diethy Diethy Amioethyl Hexanoate 5% AS is an ideal agent for regulating cabbage growth and increasing yield.